Communication Strategies used by Male and Female Students in Speaking Class: Comparative Study in Muhamadiyah University of Surakarta - Rohmawati, Dian Laila, Prof. Dr. Endang Fauziati, M. Hum, Mauly Halwat Hikmat, Ph.D (2016)
This research is mainly intended to discuss communication strategy used by male and female students. The objectives of this research are to know the types of communication strategy used by male and female students, the similarities and differences of communication strategy used, the dominance communication strategy, and the factors contributing to choosing of communication strategy by male and female students of second semester students of Muhammadiyah University of Surakarta. This research is qualitative research. The object is communication strategy on spoken production made by male and female students of the second semester of English Education Department in Muhammadiyah University of Surakarta. In collecting the data, the researcher uses naturalistic observation, video recording, and interview. In analyzing the data, the researcher does some steps which involve transcribing the video, classifying the data, quantifying, and drawing a conclusion. The result shows that male students use topic avoidance, message abandonment, circumlocution, approximation, all-purpose words, non-linguistic means, restructuring, literal translation, code-switching, retrieval, fillers, gambits, hesitation, self-initiated repair, repetition request, confirmation request, expression of non-understanding, repetition, confirmation, repair. Then female students use message abandonment, message replacement, circumlocution, approximation, all-purpose words, non-linguistic means, restructuring, literal translation, code-switching, retrieval, fillers, gambit, hesitation, self-initiated repair, self rephrasing, repetition request, appeal for help, clarification request, expression of non-understanding, repetition, and repair.